1998
DOI: 10.1088/0964-1726/7/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative impedance-based health monitoring of civil infrastructures

Abstract: This paper presents a qualitative health monitoring technique to be used in real-time damage evaluation of civil infrastructures such as bridge joints. The basic principle of the technique is to monitor the structural mechanical impedance which will be changed by the presence of structural damage. The mechanical impedance variations are monitored by measuring the electrical impedance of a bonded piezoelectric actuator/sensor patch. This mechanical-electrical impedance relation is due to the electromechanical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(138 citation statements)
references
References 4 publications
(3 reference statements)
0
122
0
3
Order By: Relevance
“…However, direct measurement for the mechanical impendence is very hard. With PZT transducers, mechanical impendence is indirectly measured as E/M one for damage detection in E/M impedance method [38].…”
Section: E/m Impedance Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct measurement for the mechanical impendence is very hard. With PZT transducers, mechanical impendence is indirectly measured as E/M one for damage detection in E/M impedance method [38].…”
Section: E/m Impedance Methodsmentioning
confidence: 99%
“…Note that the impedance measurement is often performed in ultrasonic frequency range. At such high frequencies, the dynamic response is dominated in local modes and the excitation wavelength is small enough to ensure the high sensitivity to incipient local flaws [38][39][40].…”
Section: E/m Impedance Methodsmentioning
confidence: 99%
“…By comparing the impedance signature taken in the pristine state and at any other time, structural damage can be determined. Generally, both frequency and amplitude shifts are produced relative to the pristine state (without damage) (Ayres et al, 1998;Chaudhry et al, 1995;Sun et al, 1995;Park et al, 2000;Zagrai and Giurgiutiu, 2001;Giurgiutiu et al, 2002Giurgiutiu et al, , 2004Peairs et al, 2004;Narayanan and Subramaniam, 2016a). Application of EMI technique for damage detection in concrete structures requires a careful study of the changing compliance of the substrate for different forms of damage in the substrate material from the incipient to the visible stages.…”
Section: Introductionmentioning
confidence: 99%
“…The electromechanical impedance approach using smart piezoelectric ceramic transducers having selfactuating and sensing capabilities has shown potential applications in damage detection in structural systems. Sun et al [4] and later Ayres et al [1] reported the use of piezoelectric ceramic patches (PZT) for damage detection and characterization on a laboratory-size truss structure and a prototype truss joint, respectively. The damage detection method is based on the principle of electro-mechanical coupling between the host structure and the bonded PZT patch.…”
Section: Introductionmentioning
confidence: 99%